Health- related quality of life for adult patient with chronic viral hepatitis B and C - Midhin, Adel; tawfeeq, Narmeen (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): This study aims to assess health related quality of life among Iraqi patients with chronic viral hepatitisB and C also to find out the relationship between health related quality of life and patients demographiccharacteristic and to design a new measurement scale for assessing QoL among viral hepatitis B and C patientswhich can be suitable to be adopted for Iraqi patientsMethodology: A descriptive quantitative study is carried out at Gastroenterology and Hepatology TeachingHospital from February, 1st, 2011 to August 30th 2011, Anon probability (purposive sample) of (100) chronic viralhepatitis B and C persons , who were clients of Gastroenterology and Hepatology Teaching Hospital / outpatientclinic for follow up. The data were collected through the use of semi-constructed questionnaire, which consists ofthree parts (1) demographic data form that contains (10) items (2) form medical information that contains of (7)items and (3) main domains of the quality of life which contains six main domains: physical, psychological, level ofindependence, social, environmental, spiritual domain. Content validity was determined by a panel of experts indifferent specialties. Reliability of instrument was determined by the use of test–retest approach through the pilotstudy. The data were described statistically and analyzed through use of the descriptive and inferential statisticalanalysis procedures.Results: The findings of the presented study indicate that the chronic viral hepatitis B and C affect the quality oflife domains. There is a non-significant relationship between socio-demographic characteristic and quality of lifedomains. The study concludes that the chronic viral hepatitis B and C are most common occurring among personsin urban residential area than in those in rural. chronic viral hepatitis B and C are most common in male than infemales, chronic viral hepatitis B and C are most common in married than in unmarried, chronic viral hepatitis B &C are most common in non-drink alcohol than in drink, chronic viral hepatitis B and C are most common in lowlevel education than other, chronic viral hepatitis B and C are most common in low socioeconomic status.Recommendations : the study recommended An intensive comprehensive wide population-based ( national level)studies could be conducted to assess the chronic viral hepatitis B and C patients quality of life also Health orientedmass media approach should be employed by the Ministry of Health to increase population knowledge andawareness about the route of transmission and risk factor of chronic viral hepatitis B & C and Involving bothgovernmental and non-governmental organizations in national health promotion campaign